MENINGKATKAN KOMPETENSI PEDAGOGIK DAN KINERJA GURU MELALUI MODEL SUPERVISI MANAJERIAL PEMBINAAN DIKLAT DI SD - Munawaroh, Munawaroh (Lembaga Penelitian dan Studi kebijakan MADANI Instutute, 2014)
The problems to be examined in this study are : ( a) How does an increase in teacher performance and student achievement with the implementation of Managerial Supervisory Model Development of Education and Training Students ? ( b ) How does Managerial Supervision Model Development of Education and Training and motivation on teacher performance and student learning outcomes ? study uses a quantitative approach , the data collected through the questionnaire , prepared to see the relationship between the study variables . The results showed an overview of education and training , pedagogical competence and teacher performance SDN 14 Morning Kapok West Jakarta . The results of this study also indicate that there is a positive relationship between the education and training of pedagogical, and there is also a relationship between education and training and pedagogical both jointly and individually on teacher performance . Based on the research findings , the more clearly the importance of the role of human resource development , especially the increase in competencies through education and training . With terujinya significant relationship between the independent variable and the dependent variable , then the attitude of the teacher profejonal can be improved by increasing the principal leadership , teacher discipline and condition of infrastructure facilities . Increased teacher discipline can be done through the following steps : ( 1 ) . Set goals or targets to be achieved in the near future . Create a priority order of things we want to do . ( 2 ) . Make a written schedule of activities . ( 3 ) . Perform the schedule that we created , fetapi do tenblu stiff . If necessary , we can change the schedule in accordance with the conditions and situations . (4) . Seek to constantly discipline the program schedule of activities that we already own flats . Once we do not discipline or postpone these activities , it will be difficult for us to re-do it